North Korea : - Palka, Eugene J. (McGraw-Hill/Dushkin, 2004)
Geographic Perspectives: North Korea provides a concise source of information on the physical environment and culture of the country. By examining the region through many of the sub-disciplines of geography – including historical, political, economic, urban, and medical - these guides serve as a framework to better understand current events. Included are color and black and white maps, photographs, charts, and graphs.